Contributing factors affecting job performance at private hospitals in Southern Region of Malaysia / Munirah Mohd Jidi ... [et al.] - Mohd Jidi, Munirah; Idrus, Syukurriah; Zakirai@Zakaria, Norlida; Eshak, Erratul Shela; Jamian, Nur Faithzah (UiTM Cawangan Johor, 2020)
This research explains the factors that affect job performance in private hospitals in the southern region of Malaysia. The objectives of the research were (1) to identify the relationship between salary and job performance, (2) to determine the relationship between supervision and job performance, and (3) to examine the relationship between coworkers and job performance. The research was conducted based on three hypothesis which were (1) there is relationship between salary and job performance, (2) there is relationship between co-workers and job performance, and (3) there is significant relationship between supervision and job performance. The research design chosen for this study was descriptive and inferential in nature. The selection of sample was based on the convenience sampling technique. The analysis shows that there is a positive and significant relationship between pay, colleagues, supervision and job performance.